Determination of Serum Alpha-1-Acid Glycoprotein Concentration and the Influence of Physiological and Gynecological Factors in Women Attending in Tertiary-Care Center in Mexico: A Pilot Study - Liliana García-Ortiz; Mariana Téllez-Araiza; José Gutiérrez-Salinas; Liliana Hernández-Figueroa; Juana Arellano-García; Erasmo Cordero-Martínez (Mediators of Inflammation)
Alpha 1-acid glycoprotein (AGP1) is recognized as a protein with an important immunomodulatory activity, which under certain circumstances its serum concentration is altered as a result of acute metabolic stress (e.g., infections) or chronic (e.g., obesity). This quality of altering its concentration according to the immunological circumstances of the individuals, for example, in women, in which hormonal variables, nutritional states, and/or pregnancy, has led to think that one protein can be used as a biomarker in cancer, immunological diseases, and other pathologies. The aim of the present study was to determine the concentration of AGP1 protein in serum samples of apparently healthy women and to associate this concentration with several variables, such as age, body weight, and other physiological variables, that may affect the concentration of this protein. A total of 656 apparently healthy women were included according to their clinical history, physical examination, and laboratory tests. The determination of AGP1 concentration was performed by nephelometry in serum samples. The results show that the overall mean serum concentration of AGP1 was 76.82 ± 18.63 mg/dL (range 37.95–175 mg/dL). This concentration is observed to be altered in women who presented morbid obesity (83.79 mg/dL; p <0.001); as well as in women who have had children (gestation). Our work reports for the first time the serum levels of AGP1 in Mexican women, as well as several physiological circumstances in which its concentration is modified, which should be considered if AGP1 is required as a biomarker, both in physiological and pathological circumstances.